2010
DOI: 10.1007/s00244-010-9551-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Chlorella vulgaris Growth by Cadmium, Lead, and Copper Stress and Its Restoration by Endogenous Brassinolide

Abstract: Brassinosteroids play a significant role in the amelioration of various abiotic and biotic stresses. In order to elaborate their roles in plants subjected to heavy metals stress, Chlorella vulgaris cultures treated with 10−8 M brassinolide (BL) were exposed to 10−6–10−4 M heavy metals (cadmium, lead and copper) application. Under heavy metals stress, the growth and chemical composition (chlorophyll, monosaccharides, and protein content) have been decreased during the first 48 h of cultivation. The inhibitory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 39 publications
(43 reference statements)
7
102
1
1
Order By: Relevance
“…These studies have shown that under N limitation or Cd stress, there is an increase in total lipid concentration and a decrease in growth rate. But, contrary to the findings of Bajguz (2011) that Cd at 10 À6 to 10 À4 M caused a decrease in chlorophyll a concentration of C. vulgaris, our findings show that at the environmentally relevant concentrations studied here (2 Â 10 À8 to 10 À7 M), chlorophyll a content per cell increased. This shows that the behaviour of Chlorella when exposed to environmentally relevant concentrations of Cd may differ from that shown by Chlorella exposed to very high Cd concentrations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that under N limitation or Cd stress, there is an increase in total lipid concentration and a decrease in growth rate. But, contrary to the findings of Bajguz (2011) that Cd at 10 À6 to 10 À4 M caused a decrease in chlorophyll a concentration of C. vulgaris, our findings show that at the environmentally relevant concentrations studied here (2 Â 10 À8 to 10 À7 M), chlorophyll a content per cell increased. This shows that the behaviour of Chlorella when exposed to environmentally relevant concentrations of Cd may differ from that shown by Chlorella exposed to very high Cd concentrations.…”
Section: Discussioncontrasting
confidence: 99%
“…The authors ATL and MGGM are grateful to FAPESP (2008/02078-9;2011 /09694-0), CNPq (556588/2009 314361/2009-0); MAC is grateful to TWAS, CNPq (190034/2009-2) and ABU Zaria for research funding; CCP acknowledges the Natural Sciences and Engineering Research Council of Canada.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Therefore, it is possible that plant brassinosteroids have sufficient affinity with the rat gluco-corticoid receptor protein to be connected to their signaling chain through the recognition of molecules expressed by the constitutive CaMV promoter inserted in the transformation construct. Brassinosteroids have been shown to induce tolerance to a wide range of abiotic stresses (Kagale et al, 2007;Bajguz, 2011;Sittayat et al, 2007;Arora et al, 2010a;Koh et al, 2007) through the activation of anti-oxidative stress systems (Arora et al, 2010b), as well as the enhanced synthesis of abscisic acid (Yuan et al, 2010), ethylene, salicylic acid (Divi et al, 2010), polyamines and indole-3-acetic acid (Choudhary et al, 2010(Choudhary et al, , 2011. Responses to stress in plants, moreover, are known to be activated by increased levels of auxins, which in turn determines feedback interaction with flavonoid synthetic patterns (Peer and Murphy, 2007;Lewis et al, 2011) and crosstalk with brassinosteroid transcription process (see Depuydt and Hardtke (2011) for an extensive review).…”
Section: Discussionmentioning
confidence: 99%
“…and in green algae from the Chlorella and Scenedesmus genus (Stirk and Van Staden 1997;Mazur et al 2001;Stirk et al 2004;Bajguz 2011). However, the concentration of this hormone in algal cells is somewhat lower than in vascular plants (Lau et al 2009).…”
mentioning
confidence: 99%